2019
DOI: 10.3390/microorganisms7100374
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota, Gut Health and Chicken Productivity: What Is the Connection?

Abstract: Gut microbiota and its relationship to animal health and productivity in commercial broiler chickens has been difficult to establish due to high variability between flocks, which derives from plenty of environmental, nutritional, and host factors that influence the load of commensal and pathogenic microbes surrounding birds during their growth cycle in the farms. Chicken gut microbiota plays a key role in the maintenance of intestinal health through its ability to modulate host physiological functions required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
253
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(265 citation statements)
references
References 102 publications
5
253
2
5
Order By: Relevance
“…However, in accordance with other studies, our ndings showed that the bacterial richness became relatively stable at mid-period for both breeds under the same production conditions [19,[39][40][41][42][43][44][45]. This fact evidences the importance of ock management during the production cycle in terms of the microbiota status, as the transmission between environmental and intestinal bacteria is proven [2,7,9,19,42,[46][47][48]. It is important to highlight that bacterial diversity in the intestinal tract is higher in birds with high feed e ciency [2,9,[49][50][51].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, in accordance with other studies, our ndings showed that the bacterial richness became relatively stable at mid-period for both breeds under the same production conditions [19,[39][40][41][42][43][44][45]. This fact evidences the importance of ock management during the production cycle in terms of the microbiota status, as the transmission between environmental and intestinal bacteria is proven [2,7,9,19,42,[46][47][48]. It is important to highlight that bacterial diversity in the intestinal tract is higher in birds with high feed e ciency [2,9,[49][50][51].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding gut microbiota composition, the predominant phyla obtained in this study were Firmicutes and Bacteroidetes, followed by Proteobacteria [7,9,42,45,47,54]. Thus, any alteration in the microbiota balance could lead to an alteration on the health or productivity of the breed.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Gut microbes start to colonize naturally right from the instant of hatching and perhaps even before at the time of egg laying, several microorganisms may get entry through the pores of eggshell [1][2][3]. Gut microbiota plays an essential role in feed digestibility, nutrient absorption, energy harvest and metabolism [4,5].…”
Section: Introductionmentioning
confidence: 99%